2020
DOI: 10.1111/ahe.12536
|View full text |Cite
|
Sign up to set email alerts
|

Papillary architecture in the tayra tongue

Abstract: The tayra (Eira barbara) is a mammal belonging to the Mustelidae family that occurs in all Brazilian biomes. The present work aimed to describe the morphology of the tongue of these specimens highlighting their structures and particularities that will serve as a subsidy to elucidate the anatomy of the same and for comparative studies among other species of domestic and wild animals. Five adult male specimens of E. barbara were studied, which were fixed using 10% aqueous formaldehyde solution. The tongue was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The most of the functional processes inside the oral cavity are carried out by the tongue, whose presence and description have been showed in different species of fish, demonstrating the variation in the presence of anatomical structures like taste buds, mucous cells and teeth in teleosts, also of commercial interest (Abbate et al., 2006,2017,2020a,2020b; Abbate, Guerrera, Montalbano, Ciriaco, et al., 2012; Abbate, Guerrera, Montalbano, De Carlos, et al., 2012; Alsafy, Bassuoni, & Hanafy, 2018; Amato et al., 2012; Dos Santos, Arantes, Santiago, & Dos Santos, 2015; El Bakary, 2014; Elgendy, Alsafy, & Tanekhy, 2016; Germanà et al., 2009; Guerrera et al., 2015; Ikpegbu, Ibe, & Nlebedum, 2019; Kasumyan, 2019; Kettratad, Senarat, Boonyoung, & Jiraungkoorsku, 2017; Levanti et al., 2017; Mahmoud, Essa, & Sayed, 2016; Sadeghinezhad, Rahmati‐holasoo, Fayyaz, & Zargar, 2015; Sayed, Mahmoud, & Essa, 2019; Yu et al., 2019). Several significant papers, important as comparative data, are present in the literature in upper vertebrates like birds, reptiles and mammals (Abbate et al, 2008, 2009, 2010, 2020b; Abumandour & Kandyel, 2020; Barbosa et al., 2020; Bels et al., 2020; Cizek, Hamouzova, Goździewska‐Harłajczuk, Klećkowska‐Nawrot, & Kvapil, 2020; Cizek, Hamouzova, Kvapil, & Kyllar, 2019; Emura, 2016a,2016b,2016c,2017,2018a,2018b,2018c,2018d,2019; Erdoğan & Alan, 2012; Erdoğan & Iwasaki, 2014; Erdoğan Lima & Pérez, 2016; Erdoğan Villar Arias & Pérez, 2016; Erdoğan, Villar Arias, et al., 2016; Erdoğan et al., 2018a; Erdoğan and Sağsöz, 2018b; Freire et al., 2019; Gonçalves et al., …”
Section: Introductionmentioning
confidence: 99%
“…The most of the functional processes inside the oral cavity are carried out by the tongue, whose presence and description have been showed in different species of fish, demonstrating the variation in the presence of anatomical structures like taste buds, mucous cells and teeth in teleosts, also of commercial interest (Abbate et al., 2006,2017,2020a,2020b; Abbate, Guerrera, Montalbano, Ciriaco, et al., 2012; Abbate, Guerrera, Montalbano, De Carlos, et al., 2012; Alsafy, Bassuoni, & Hanafy, 2018; Amato et al., 2012; Dos Santos, Arantes, Santiago, & Dos Santos, 2015; El Bakary, 2014; Elgendy, Alsafy, & Tanekhy, 2016; Germanà et al., 2009; Guerrera et al., 2015; Ikpegbu, Ibe, & Nlebedum, 2019; Kasumyan, 2019; Kettratad, Senarat, Boonyoung, & Jiraungkoorsku, 2017; Levanti et al., 2017; Mahmoud, Essa, & Sayed, 2016; Sadeghinezhad, Rahmati‐holasoo, Fayyaz, & Zargar, 2015; Sayed, Mahmoud, & Essa, 2019; Yu et al., 2019). Several significant papers, important as comparative data, are present in the literature in upper vertebrates like birds, reptiles and mammals (Abbate et al, 2008, 2009, 2010, 2020b; Abumandour & Kandyel, 2020; Barbosa et al., 2020; Bels et al., 2020; Cizek, Hamouzova, Goździewska‐Harłajczuk, Klećkowska‐Nawrot, & Kvapil, 2020; Cizek, Hamouzova, Kvapil, & Kyllar, 2019; Emura, 2016a,2016b,2016c,2017,2018a,2018b,2018c,2018d,2019; Erdoğan & Alan, 2012; Erdoğan & Iwasaki, 2014; Erdoğan Lima & Pérez, 2016; Erdoğan Villar Arias & Pérez, 2016; Erdoğan, Villar Arias, et al., 2016; Erdoğan et al., 2018a; Erdoğan and Sağsöz, 2018b; Freire et al., 2019; Gonçalves et al., …”
Section: Introductionmentioning
confidence: 99%
“…31 The three-dimensional analysis revealed that the filiform papillae were elongated and conical in shape, located in the rostral and middle regions of the tongue, and CTCs had conical shapes. The shape of the filiform papilla differed from the trifurcated forms, 2 and from studies that demonstrate two distinct morphologies. 1,32,33 The morphologies of the filiform papillae can be subclassified into the following subtypes: two (insectivorous bat); 23 three (fruit bat); 21,23 four (New Zealand white rabbits); 34 or six (fruit bats).…”
Section: Discussionmentioning
confidence: 99%
“…The three-dimensional morphology of the vallate papillae is similar to that of the feral cat, 17 but differs from the pig in the absence of the annular projection. 32 Also, the morphology of the vallate papilla can be rounded, 2 and rounded with an annular pad. 13 The irregular projections found on the surface of the vallate papilla are similar to the pseudo papillae described for wild boar and pigs.…”
Section: Figure 3 Transmission Electron Microscopy Of the Dorsal Epithelium Of The Tongue Of The Wild Boar A) The Epithelial Cells Of Thementioning
confidence: 99%
See 2 more Smart Citations